KOMPETENSI PAEDAGOGIK GURU PENDIDIKAN AGAMA ISLAM TERHADAP MOTIVASI BELAJAR SISWA SMP - Ujang Dedih; Ai Irma Nurajijah (Jurnal Perspektif, 2018)
The purpose of this study was to determine the reality of student responses to the teacher's paedagogic competence; to find out the reality of student learning motivation to take PAI lessons; and to find out the reality of the relationship between student responses to the competence of PAI teachers with their learning motivation in participating in PAI lessons. what is used in this study is the correlation method. While the data collection technique uses observation and questionnaire distributed to 34 class VIII students of SMPN 17 Kota Bandung as respondents. Quantitative data were obtained and analyzed using statistical analysis. From the results of the study it was found that: the reality of student responses to the teacher's paedagogic competence is included in the high qualification, this is evident from the results of the average score of 15 questionnaire question items that were submitted at 4.21; the reality of students' learning motivation to participate in PAI subjects is included in high qualifications, this is evident from the results of the average score of 15 questionnaire questions asked for 4.05.